SOLUTIONS TO OVERCOME THE CHALLENGES OF CHARACTER EDUCATION AND STUDENTS' MENTAL RESILIENCE IN THE RECONSTRUCTION OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM POST-GLOBAL CRISIS - rosyida1, Kholadatur; Rizal, Mohammad Syifaur; Mundiri, Akmal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Character education that integrates Islamic religious values, a holistic approach to learning, and technology use are essential factors in shaping students' mental resilience and ability to overcome life's challenges. The research method used is a qualitative approach with a case study design involving in-depth interviews with Islamic Religious Education teachers, students, and educational psychologists, as well as classroom observations to explore the application of the curriculum in the field. Thematic analysis techniques were used to identify patterns relevant to the research objectives. The study results indicate that integrating character values in the Islamic Religious Education curriculum, such as patience, trust, and honesty, can improve students' mental resilience, helping them deal with anxiety and post-crisis stress. A holistic approach to teaching that includes cognitive, emotional, and social aspects has proven effective in improving students' understanding of religious teachings and shaping resilient characters. In addition, using technology in Islamic Religious Education learning also increases student engagement, provides more flexible access to teaching materials, and strengthens students' abilities to manage their emotional challenges. This study contributes to developing an Islamic Religious Education curriculum that is more adaptive and relevant to students' needs in the post-crisis era and provides recommendations for developing more comprehensive learning and supporting students' mental resilience.